Extinction and Non-Extinction of Solutions to a p-Laplace Equation with a Nonlocal Source and an Absorption Term - Han, Yuzhu; Li, Haixia; Gao, Wenjie (Mathematical Modelling and Analysis, 2014)
In this short paper, the authors investigate the extinction and non-extinction of solutions to a fast diffusive p-Laplace equation with a nonlocal source and an absorption term. By applying the super-solution and sub-solution methods, instead of energy estimate methods, they give a classification of the exponents and coefficients for the solutions to vanish in finite time or not, which generalizes some previous results.